2007
DOI: 10.1007/s10827-007-0057-3
|View full text |Cite
|
Sign up to set email alerts
|

A model for modulation of neuronal synchronization by D4 dopamine receptor-mediated phospholipid methylation

Abstract: We describe a new molecular mechanism of dopamine-induced membrane protein modulation that can tune neuronal oscillation frequency to attention-related gamma rhythm. This mechanism is based on the unique ability of D4 dopamine receptors (D4R) to carry out phospholipid methylation (PLM) that may affect the kinetics of ion channels. We show that by deceasing the inertia of the delayed rectifier potassium channel, a transition to 40 Hz oscillations can be achieved. Decreased potassium channel inertia shortens spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 120 publications
0
23
0
Order By: Relevance
“…Dopamine modulation of fast rhythmic neuronal synchronization has been suggested by several authors (Whittington et al, 2011; Furth et al, 2013) and simulated from artificial neuronal networks (Kuznetsova and Deth, 2008; Kömek et al, 2012). Dopamine modulation of γ oscillations has been described in the hippocampus (Weiss et al, 2003; Wójtowicz et al, 2009; Andersson et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…Dopamine modulation of fast rhythmic neuronal synchronization has been suggested by several authors (Whittington et al, 2011; Furth et al, 2013) and simulated from artificial neuronal networks (Kuznetsova and Deth, 2008; Kömek et al, 2012). Dopamine modulation of γ oscillations has been described in the hippocampus (Weiss et al, 2003; Wójtowicz et al, 2009; Andersson et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…Most of these drugs are aimed at normalizing the electrochemical balance of the injured brain to optimize its ability to heal and minimize secondary injury. Dopaminergic medications have also been shown to promote gamma band activity during attention through D4 receptor activation (Kuznetsova and Deth, 2008). Nicotinamide too may help reverse severe oxidation, likely through mitochondrial mechanisms (Shetty et al, 2014), and some authors have suggested that blockade of AMPK in acute brain injury may protect against zinc neurotoxicity (Eom et al, 2016).…”
Section: The Biology Of Neurological Injurymentioning
confidence: 99%
“…After exogenous dopamine stimulation the coherence frequency increased to 70-85 Hz. A neurochemical mechanism for this effect is suggested by Kuznetsova and Deth (2008). They found that dopamine, acting on D4 receptors, promotes synchronization of oscillations in cortical pyramidal cell-interneuron networks.…”
Section: The Saliency Detection Hypothesismentioning
confidence: 99%